DIVERSITY AND POTENTIAL OF MEGACHIROPTERA BAT AS DISPERSAL AND POLINATOR AT HARAPAN RAINFOREST, JAMBI: DIVERSITAS DAN POTENSI KELELAWAR MEGACHIROPTERA SEBAGAI DISPERSER DAN POLINATOR DI HUTAN HARAPAN, JAMBI - fitria ramona (BIO-SITE |Biologi dan Sains Terapan, 2019)
Abstract Diversity and potential of Megachiroptera bat as dispersal and polinator was conducted to know diversity of Megachiroptera bats at Harapan Rainforest, potential of Megachiroptera bats as dispersal seed and pollinator and to know the daily activity of Megachiroptera bats pollinate and disperse the seeds of plants in Harapan Raiforest, Jambi . We used purposive sampling method using mist net were installed 90 traps – night. The result showed that five species of Megachiroptera bat are Cynopterus brachyotis , C. horsfieldi , C. sphinx , C. titthaecheilus and Macroglossus minimus with index of diversity value and evenness index are relatively low about 0.99 and 0.62. Kinds of Megachiroptera bats potentially as dispersal are C. brachyotis , C. horsfieldi , C. sphinx , and C. titthaecheilus and bats potentially as pollinator are C. brachyotis , C. sphinx and M. minimus. The pattern of time daily activity of Megachiroptera bats as disperse seeds and pollinate plants in Harapan Rainforest by C. sphinx and C. brachyotis was whole of night with peak activity C. sphinx at night ( 21:00 pm to 00:00 am) and C. brachyotis at end of night ( 3:00-6:00 am ). Key word : Megachiroptera bat, dispersal, polinnator, Harapan Rainforest